2015
DOI: 10.1007/s00228-015-1865-4
|View full text |Cite
|
Sign up to set email alerts
|

A review on colistin nephrotoxicity

Abstract: Colistin is a nephrotoxic antibiotic; a worldwide increase in nosocomial infections has led to an increase in its usage. Nephrotoxicity is the concerning adverse effect of this drug. The mechanism of nephrotoxicity is via an increase in tubular epithelial cell membrane permeability, which results in cation, anion and water influx leading to cell swelling and cell lysis. There are also some oxidative and inflammatory pathways that seem to be involved in colistin nephrotoxicity. Risk factors of colistin nephroto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
132
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 215 publications
(159 citation statements)
references
References 56 publications
4
132
1
7
Order By: Relevance
“…All are closely related to the worsening of renal functions. The available literature shows that the COL dose, duration of therapy, co-administration of nephrotoxic agents, age, sex, underlying diseases, hypoalbuminemia, and severity of the disease are closely related to COL-associated risk factors [6]. NAC is a common option for maintaining airway clearance [13], so these data are particularly important for ICUs that use nephrotoxic agents intensively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All are closely related to the worsening of renal functions. The available literature shows that the COL dose, duration of therapy, co-administration of nephrotoxic agents, age, sex, underlying diseases, hypoalbuminemia, and severity of the disease are closely related to COL-associated risk factors [6]. NAC is a common option for maintaining airway clearance [13], so these data are particularly important for ICUs that use nephrotoxic agents intensively.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury (AKI) is a frequent adverse effect of COL, with an incidence of 8-58%, particularly at high doses [4,5]. Nephrotoxicity is usually reversible but can sometimes result in chronic kidney disease (CKD) [6]. Oxidative stress plays an important role in the pathogenesis of COL-induced nephrotoxicity so the protective effects of antioxidative agents, such as ascorbic acid, lycopene, and N-acetylcysteine [NAC] have been investigated recently [2,7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Dalfino et al (54) suggested a new dose adjustment for high-dose colistin therapy for patients with renal insufficiency. For patients with creatinine clearance of 20 to 50 ml/min, they recommend a loading dose of 9 MU and maintenance doses of 4.5 MU every 24 h. For patients with creatinine clearance of Ͻ20 ml/min, they recommend a loading dose of 9 MU and maintenance doses of 4.5 MU every 48 h (21,55).…”
Section: Use Of Colistin In Human and Veterinary Medicine Use In Humamentioning
confidence: 99%
“…Neurotoxicity is dose dependent and reversible (55) and may cause peripheral and facial paresthesia, weakness, dizziness/vertigo, visual disturbances, confusion, ataxia, and neuromuscular blockade, even leading to respiratory failure or apnea (56). The most common neurotoxicological effect is paresthesia (occurring in 27% of patients), and there is no report of neuromuscular blockade or apnea in the recent literature (56).…”
Section: Use Of Colistin In Human and Veterinary Medicine Use In Humamentioning
confidence: 99%
See 1 more Smart Citation